L'eredità di Bramante Tra spazio virtuale e proto-design - Rossi, Michela; Russo, Michele (Forme del disegno, 2021)
Bramante's skill in controlling the creation of a seamlessly conceived space shows how architecture can exploit its representative capacity of internal perspectives, considered architecture integration. The key adopted to reach this result is the "architectura picta" of the built space. It adopts built space combined with small apparatuses to conceal the critical points in which the continuity between real and virtual space is resolved. The multiplication of centers amplifies the effectiveness of the perspective, making it convincing from several points of view, even for a moving observer. The implicit perceptual effect overcomes the geometric correctness, which was neglected to enhance its effectiveness as a tool for creating a global and augmented art "ante litteram". The research published in this volume documents, through a small number of selected cases studies, the unsuspected development in Lombardy in applying perspective decoration to architecture, understood in the broadest sense as the art of constructing artificial space. This latter consists of controlling the instruments of representation to improve perceptive involvement and visual communication. It underlines the continuity of Milanese perspective with the immersive spaces of augmented reality offered today by digital technology.